END-CRETACEOUS CALCAREOUS NANNOPLANKTON AND RESPONSE TO THE K/Pg EVENT IN THE KAWAS EPICONTINENTAL SEA. INSIGHTS FROM CERRO BOMBERO SECTION, JAGÜEL FORMATION, NEUQUÉN BASIN - Pérez Panera, Juan Pablo (2024)
Fil: Talevi, Marianella. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro; Argentina.